Internet Impacts on Parent–Child Communication in Vietnamese Urban Families. - Nguyen, Lan Thi Thai; Le, Thi Kim Dung; Tran, Van Cong; Nguyen, Duc Nam; Nguyen, Hong Kien; Le, Duy Dung (Child & Family Social Work, 2025)
With 72% of Vietnamese households using the Internet after Vietnam first had access in November 1997, the traditional culture of parent–child communication within families in particular has been significantly influenced by the arrival of this technology. This paper presents a mixed‐method study that surveyed 464 parent–child dyads, conducted 30 in‐depth interviews and 6 group discussions held in three major cities across Vietnam. The results demonstrate how the parents and their children use the Internet and recognize the influence of this technology on their communication. It is apparent that despite the old ways of a top‐down or hierarchical relationship in traditional homes, parent–child communication is moving in the direction of a more equal and open manner despite some disparities in the understanding and respecting of each other's emotions and perspectives due to conflicts created by generational gaps and cultural understandings. The positive and negative impacts of the Internet on parent and child communication are acknowledged, but this study advocates for a change from informal communication rules related to Internet usage and suggests developing a professional system that supports parents and children to manage the parent–child communication issues and challenges more effectively.